OPEC and the world oil market : the genesis of the 1986 price crisis - Mabro, Robert, ed. (Oxford UP OxfordGB, 1986)
Traces the historical development of OPEC's crises during 1974-86 and proposes remedial policies and strategies. Discusses the policies of OPEC in a slack oil market and suggests solutions to the oil price differential problem. Outlines the role, objectives, and policies of Saudi Arabia in OPEC. Discusses market stability and security from the consumers' point of view and identifies problems and prospects within the industry. Includes interventions of participants. Proposes stabilization and long-term price strategies for OPEC.